Nonequilibrium and quantum coherent phenomena in the electromechanics of suspended nanowires (Review Article) - Shekhter, Robert I.; Santandrea, Fabio; Sonne, Gustav; Gorelik, Leonid Y.; Jonson*, Mats (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Strong coupling between electronic and mechanical degrees of freedom is a basic requirement for the operation of any nanoelectromechanical device. In this Review we consider such devices and in particular investigate the properties of small tunnel-junction nanostructures that contain a movable element in the form of a suspended nanowire. In these systems, electrical currents and charge can be concentrated to small spatial volumes resulting in strong coupling between the mechanics and the charge transport. As a result, a variety of mesoscopic phenomena appear, which can be used for the transduction of electrical currents into mechanical operation. Here we will in particular consider nanoelectromechanical dynamics far from equilibrium and the effect of quantum coherence in both the electronic and mechanical degrees of freedom in the context of both normal and superconducting nanostructures.